2011
DOI: 10.1007/s00595-011-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

An annular pancreas associated with carcinoma of the papilla of Vater: report of a case

Abstract: An annular pancreas is an uncommon congenital anomaly that usually presents early in childhood. Malignancy in the setting of an annular pancreas is unusual. We herein report a case of annular pancreas with carcinoma of the papilla of Vater. A 59-year-old man presented with epigastric discomfort and was referred to us after gastroduodenal endoscopy showed a tumor of the papilla of Vater. Preoperative imaging showed the pancreatic parenchyma encircling the descending duodenum and a tumor at the papilla of Vater.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…AP was first described by Tiedemann in 1818 and was termed Bannular pancreas^in 1862 by Ecker. The first successful surgery for an annular pancreas, a gastrojejunostomy, was performed in 1905 by Vidal [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AP was first described by Tiedemann in 1818 and was termed Bannular pancreas^in 1862 by Ecker. The first successful surgery for an annular pancreas, a gastrojejunostomy, was performed in 1905 by Vidal [3].…”
Section: Discussionmentioning
confidence: 99%
“…A review of the 106 cases by Yogi et al [6] found nine (8.5 %) having a pancreaticobiliary malignancy (five ampullary carcinomas, two pancreatic carcinomas, and two cholangiocarcinomas). Previously, only seven cases of ampullary carcinoma with AP have been reported in the English literature [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients undergoing endoscopic retrograde cholangiopancreatography (ERCP), approximately one in 1000 examined cases was found to have the annular pancreas [ 3 , 12 ]. In these cases, ERCP may not always be successful, due to technical difficulty in some cases, particularly in cases with the duodenal ulcer and/or stenosis of the descending part of the duodenum [ 13 ]. In most cases, multi-slice CT shows the circumferential pancreatic parenchyma around the descending part of the duodenum [ 13 , 14 ]; however, in some cases, this imaging method may lead to misinterpretation as a thickening of the duodenum [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, ERCP may not always be successful, due to technical difficulty in some cases, particularly in cases with the duodenal ulcer and/or stenosis of the descending part of the duodenum [ 13 ]. In most cases, multi-slice CT shows the circumferential pancreatic parenchyma around the descending part of the duodenum [ 13 , 14 ]; however, in some cases, this imaging method may lead to misinterpretation as a thickening of the duodenum [ 15 ]. With this in mind, magnetic resonance imaging (MRI) and MRCP are useful for understanding anomalies observed in the pancreatic anatomy [ 13 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%